Molecular Detection, Phylogenetic Analysis and Differentiation of Fowl Adenovirus from Chickens with Inclusion Body Hepatitis in Haryana - Kumar, Aman; Ranjan, Koushlesh; Prasad, Minakshi; Mahajan, Nand Kumar; Maan, Sushila (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Inclusion Body Hepatitis (IBH) is responsible for huge economic losses to the poultry industry and is caused by Fowl adenoviruses (FAdV). A total of thirty pooled poultry liver homogenates from thirty different poultry farms suspected of IBH have been processed for the PCR-based detection and chicken embryo liver cell culture-based virus isolation. Out of 30 pooled samples, 18 were found positive in PCR; however, only 9 chicken embryo liver cell culture samples having CPE found positive in PCR. The nucleic acid obtained from FAdV specific Polymerase Chain Reaction (PCR) were further genotyped by in-silico restriction enzyme analysis (REA) using enzymes BsiWI, KpnI, and HpaI. Upon phylogenetic analysis, all the nine positive samples of FAdVs clustered in distinct clads of FAdV serotypes 8a, 8b, and 11, which is in correlation with the REA pattern. Thus, nucleic acid sequencing followed by phylogenetic analysis revealed the presence of FAdV-D (serotype 11) and FAdV-E (serotype 8a and 8b) in broiler chickens.